Insights into the Virulence of Campylobacter jejuni Associated with Two-Component Signal Transduction Systems and Single Regulators - GAHAMANYI NOEL; Song, Dae-Geun; Mboera, Leonard E. G.; Matee, Mecky I.; Mutangana, Dieudonn？; Amachawadi, Raghavendra G.; Komba, Erick V. G.; PAN, CHEOL HO (MDPI AG, 2022)
Campylobacter jejuni is one of the major aetiologies of diarrhoea. Understanding the processes and virulence factors contributing to C. jejuni fitness is a cornerstone for developing mitigation strategies. Two-component signal transduction systems, known as two-component systems (TCSs), along with single regulators with no obvious cognate histidine kinase, help pathogens in interacting with their environments, but the available literature on C. jejuni is limited. A typical TCS possesses histidine kinase and response regulator proteins. The objective of this review was to provide insights into the virulence of C. jejuni associated with TCSs and single regulators. Despite limited research, TCSs are important contributors to the pathogenicity of C. jejuni by influencing motility (FlgSR), colonisation (DccRS), nutrient acquisition (PhosSR and BumSR), and stress response (RacRS). Of the single regulators, CbrR and CosR are involved in bile resistance and oxidative stress response, respectively. Cross-talks among TCSs complicate the full elucidation of their molecular mechanisms. Although progress has been made in characterising C. jejuni TCSs, shortfalls such as triggering signals, inability to induce mutations in some genes, or developing suitable in vivo models are still being encountered. Further research is expected to shed light on the unexplored sides of the C. jejuni TCSs, which may allow new drug discoveries and better control strategies.